Numerical investigation of two-dimensional thermally assisted ductile regime milling of nanocrystalline hydroxyapatite bioceramic material. Issue 3 (April 2015) - Ma, Jianfeng; Ge, Xianchen; Pelate, Nathan; Lei, Shuting
Abstract: This study investigates the effects of different variables (preheating temperature, edge radius, and rake angle) on ductile regime milling of a bioceramic material known as nanohydroxyapatite (nano-HAP) using numerical simulation. Commercial software AdvantEdge FEM Version 6.1 is used to conduct the simulation of 2D milling mimicked by orthogonal machining with varying uncut chip thickness. Thermal boundary conditions are applied to approximate preheating of the work material. Based on the pressure-based criterion for ductile regime machining (DRM), the dependence of critical depth of cut on cutting conditions is investigated. It is found that as uncut chip thickness decreases, the critical depth of cut decreases. In addition, the critical depth of cut increases as the negativity of rake angle and/or preheating temperature increase.